Tourism as Memory-Making Russian Tourism in the Shadow of Empire - Pfoser, Alena; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
(3z(BThis book makes a timely and much anticipated intervention in scholarship on tourism and memory-making. Alena Pfoser$1 (Bs insightful, illuminating and rigorously researched analysis of Russian encounters at three former Soviet destinations demonstrates the methodological and conceptual potential of taking tourism seriously in our efforts to comprehend contemporary cultural memory.(3y $1 (BDr Jessica Rapson, King$1 (Bs College London Until recently the Russian Federation used to be one of the largest markets for outbound travel. Among Russians$1 (Bfavourite destinations were cities that used to be part of the Russian Empire and the Soviet Union, and are now located in the independent nation-states bordering Russia. This open access book provides an empirically rich and conceptually sophisticated account of the mnemonic interactions between Russians and their neighbours in the shadow of empire and geopolitical confrontations. Based on extensive ethnographic research with tourists and tour guides in the cities of Tallinn, Kyiv, and Almaty before Russia$1 (Bs full-scale war on Ukraine, it analyses the practices through which cultural memories are performed in tourism encounters, as well as the forms they take. Imperial nostalgia, the production and consumption of national pasts, and memory diplomacy are discussed as key modes of remembering in tourism. Through the case of Russian tourism, the book argues for an invigoration of research on memory and tourism, which despite the significance of tourism for the circulation of cultural memories has so far received surprisingly little attention. Bringing debates in memory, heritage and tourism studies into a dialogue, the book expands the field of study beyond museums and heritage sites and puts forward a transnational approach that acknowledges diverse and entangled modes of remembering in tourism, situates memory-making in a wider political context and reflects on its geopolitical implications. Alena Pfoser is Senior Lecturer in Communication and Media Studies at Loughborough University, UK.s
1. Introduction -- 2. Tourism as memory-making.-3. Travelling across a post-imperial space -- 4. Walking through multi-layered histories -- 5. Remembering a shared homeland -- 6. Encountering other pasts -- 7. Navigating contested pasts -- 8. The (geo)politics of tourism memories.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Collective memory; Russia -- History; Europe, Eastern -- History; Soviet Union -- History; Cultural property; Civilization -- History; Memory Studies; Russian, Soviet, and East European History; Cultural Heritage; Cultural History